Spel as an Improvisational System in East Javanese Ludruk: Spel sebagai Sistem Improvisasi dalam Pertunjukan Ludruk Jawa Timur - Autar Abdillah; Indar Sabri; Arif Hidajad; Syaiful Qadar Basri; Welly Suryandoko (Jurnal Pendidikan Sendratasik, 2025)
Improvisation is a central device that sustains the flexibility, social proximity, and vitality of ludruk performance. Yet the local practice known as spel is commonly reduced to a technical pre-performance meeting, leaving its artistic and pedagogical mechanisms insufficiently conceptualized. This study identifies the distinctive features of spel and develops a conceptual model of improvisation in East Javanese ludruk. An exploratory qualitative approach combines literature review, performance observation, structured and unstructured interviews with ludruk practitioners, document analysis, and source-method triangulation. Findings at the progress-report stage indicate that spel functions as a coordination system connecting narrative maps, scene nodes, bodily and vocal cues, inter-performer rhythm, audience-response reading, and ethical boundaries of humour. Ludruk improvisation is therefore not unstructured spontaneity but real-time co-creation supported by experience, ensemble trust, and cultural knowledge. The article proposes a five-stage spel cycle and contributes to improvisation studies, traditional actor pedagogy, and the regeneration of ludruk. Kata kunci: spel; improvisasi; ludruk; dramaturgi; regenerasi